The Implementation of Substitution Drill in Teaching Simple Present Tense - Lutfiyah Lutfiyah; Irma Savitri Sadikin; Farhan Fuady; Rikzan Kurniawan Hidayat; Yudis Frandikta (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The study aimed to find out the effectiveness of substitution drill in teaching simple present tense. This study discussed about the treatment given for the language ability especially in Simple Present Tense. The method is used quantitative research. The data collection technique in this study used pre - test and post - test. The subject is 32 eighth grade students. In the process of English learning, the problem came up in grammar part, especially for simple present tense. Students have difficulty in this teaching learning process. It was caused many students are studying at home due to the COVID-19 disease. These teaching and learning activities have been carried out online, making the activities indirectly felt monotonous, getting bored and even stressed by the online learning situation. Students are increasingly lacking enthusiasm for learning because they found difficulties to understand the material explained by the teacher. Then, students may experience decreased motivation to study at home, because it is difficult to focus while studying online.  As the result and conclusion of this study, that substitution drill was an effective technique, it could improve students’ ability in learning simple present tense.